2006
DOI: 10.1002/qua.20985
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical study of cyclic dipeptides

Abstract: ABSTRACT:The preferred conformations of cyclic dipeptides were first studied systemically using the density functional theory (DFT) B3LYP method at the 6-31G(d) level. The structural characteristics of cyclic dipeptides were revealed, most of which have not been confirmed until now. Our studies showed that the six-member main circles of cyclic dipeptides composed of natural l-amino acid residues appeared as boat conformations. The important factors that influence conformations of cyclic dipeptides, such as mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…They concluded that the energetically favourable conformers adopt a boat configuration in solution, with respect to the DKP ring. Zhu et al 19 calculated the structures of all of the cyclic peptides consisting of the same two amino acids, including cPhePhe, and found that they adopted the boat conformation. We recently summarised other previous studies of cyclic dipeptides.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the energetically favourable conformers adopt a boat configuration in solution, with respect to the DKP ring. Zhu et al 19 calculated the structures of all of the cyclic peptides consisting of the same two amino acids, including cPhePhe, and found that they adopted the boat conformation. We recently summarised other previous studies of cyclic dipeptides.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Surprisingly, despite the large amount of experimental spectroscopic data reported for cyclo(Gly-Gly), [18 -21] relatively little work has been reported on the vibrational spectra of other cyclic peptide molecules that contain the cis-peptide group. The current study is part of a long-term program to investigate the relationship between vibrational spectroscopic characteristics and molecular structure of CDAPs.…”
Section: Introductionmentioning
confidence: 99%
“…A boat conformation was, consistently, shown to be the most stable gas-phase conformation. [20] The foregoing study primarily focused on a comparison of the boat and chair conformers of CDAPs; experimental data and normal coordinate analyses were not reported.…”
Section: Geometry Optimizationsmentioning
confidence: 99%
“…[10] X-ray crystallography, [11 -15] NMR, [16,17] CD [18] and gas-phase microwave [19] spectroscopic techniques have hitherto been used in investigating the structure and conformation of a number of symmetrically substituted CDAPs. Theoretical spectroscopic investigations [20] have also played a part in structural analysis. [21] Despite the foregoing comments, detailed experimental vibrational spectroscopic experiments on CDAPs have, to date, been less common except for, e.g., the studies on the parent DKP (i.e.…”
Section: Introductionmentioning
confidence: 99%